Mood and judgments based on sequential sampling - Fiedler, Klaus; Renn, Sven-Yves; Kareev, Yaakov (Journal of behavioral decision making, 2010)
Different adaptive styles characterize cognition and behavior in different affective states. Whereas negative affect supports accommodation (i.e., stimulus-driven bottom-up processing), positive affect supports assimilation (i.e., self-determined top-down processing). Applying this well-established rule to binary choices after self-truncated information sampling, we predicted that positive mood should render choices less dependent on large samples than negative mood. Consequently, the potential primacy advantage underlying Wald's (1947) sequential testing (i.e., quick and correct decisions from the first few items in a sample) was exploited more efficiently when participants were in positive rather than negative mood. This efficient utilization of small samples in positive mood was obtained under the very conditions derived on a priori ground from a statistical model, namely, when a response criterion or threshold was high and when the true difference between choice options was relatively small. Copyright © 2009 John Wiley & Sons, Ltd.
Gesehen am 17.12.2020